From Transactional to Partnership: The Strategic Role of "Rembug Pawon” in CRM Implementation for Customer Loyalty in Koperasi Sridonoretno - Bintang Permata Putri; Natasya Ika Suryaningsih; Sudarmiatin Sudarmiatin; Ita Prihatining Wilujeng (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The growth of the Indonesian coffee industry has seen increased competition among business actors, including farmer cooperatives that play a strategic role in the agribusiness supply chain. Koperasi sridonoretno faces challenges in maintaining customer loyalty and increasing product value amidst intense market competition and volatile coffee prices. This study aims to analyze the strategic role of the "Rembug Pawon" forum in implementing Customer Relationship Management (CRM) to strengthen customer loyalty and relationships at the Sridonoretno Cooperative. A qualitative descriptive approach was used through observations and in-depth interviews with the cooperative's chairman and members. Data were then analyzed using the IDIC (Identify, Differentiate, Interact, Customize) Model. The research findings indicate that Rembug Pawon serves as an interactive and collaborative platform between the cooperative, farmers, and customers, and plays a crucial role in transforming relationships from transactional to partnership-based. Through this forum, the cooperative identifies key customers, differentiates services according to their needs, maintains intensive interactions, and customizes products based on customer preferences. The implementation of community-based CRM through Rembug Pawon has proven effective in fostering sustainable partnerships and building emotional strength from customers based on trust and loyalty. These results indicate that a community-oriented CRM strategy can strengthen customer relationships and increase cooperative competitiveness in the dynamic coffee industry.